PRIMARY CLASS IN THEIR STUDENT’S ECOLOGICAL EDUCATION OF FORMATION PEDAGOGICAL FEATURES - Omonturdiyeva Mahliyo Ochil qizi (Scholar Express Journal, 2023)
Todays in the day initial class to his student’s ecological education to give in the process nature save competencies form, to nature reasonable in relation being, nature laws and events about creative thinking development, ecological education based on ecological values absorb through initial class in their students ecological knowledge and skills to develop reach.
Keywords: ecology; nature; ecological education; environment